13. Factors related to suicidal behavior in adolescents at the Vietnam National Children's Hospital from 2020 - 2022 - Vinh, Ngo Anh; Loan, Do Minh (Tạp chí Nghiên cứu Y học, 2023)
This is a prospective study on 32 children with suicidal behavior who came to the National Children’s Hospital for examination and treatment from February 2020 to September 2022. There were more girls than boys (71.9%% vs 28.1%). There is a relationship between the child -parents, father-mother with the child’s suicidal behavior. The main events leading to children’s suicidal behavior are mainly related to the family and school environment, accounting for 87.5%, 62.5% children are introverted, 28.1% children have suicidal ideation and behavior and 18.8% of cases had self-destructive behavior. 81.2% of children showed warning signs before committing suicide. Suicide is more common in girls. Family relationships between parents and children are related to children’s suicidal behavior. The main events associated with suicidal behavior are primarily in the home and school settings. We recommend that children should be examined when they show warning signs related to suicide.